Photodetection and transport properties of surface capped silicon nanowires arrays with polyacrylic acid - Kamran Rasool; M. A. Rafiq; Mushtaq Ahmad; Z. Imran; S. S. Batool; M. M. Hasan (AIP Advances, 2013)
Efficient hybrid photodetector consisting of silicon nanowires (SiNWs) (∼40 μm) capped with Polyacrylic Acid (PAA) is demonstrated. Highly diluted PAA with deionized (DI) water was spun directly on vertical SiNW arrays prepared by metal assisted electroless chemical etching (MACE) technique. We have observed ∼9, 4 and 9 times enhancement in responsivity, detectivity and external quantum efficiency in SiNWs/PAA hybrid device in comparison to SiNWs only device. Higher electrical current and photodetection may be due to the increment of hydrophilic content (acceptor like states) on SiNWs interface. The higher photosensitivity can also be attributed to the presence of low refractive index PAA around SiNWs which causes funneling of photon energy into SiNWs. Surface roughness of SiNWs leads to immobilization of charge carriers and hence shows persistent photoconductivity.